Hierarchy and positive/negative interplays of the hepatocyte nuclear factors HNF-1, -3 and -4 in the liver-specific enhancer for the human alpha-1-microglobulin/bikunin precursor. - Rouet, P (1995)
Alpha-1-microglobulin and bikunin are two plasma glycoproteins encoded by an alpha-1-microglobulin/bikunin precursor (AMBP) gene. The strict liver-specific expression of the AMBP gene is controlled by a potent enhancer made of six clustered boxes numbered 1-6 that have been reported to be proven or potential binding sites for the hepatocyte-enriched nuclear factors HNF-1, -4, -3, -1, -3, -4, respectively. In the present study, electromobility shift assays of wild-type or mutated probes demonstrated that the boxes 1-5 have a binding capacity for their cognate HNF protein. Box 5 is also a target for another, as yet unidentified, factor. A functional analysis of the wild-type or mutated enhancer, driving its homologous promoter and a reporter CAT gene in the HepG2 hepatoma cell line, demonstrated that all six boxes participate in the enhancer activity, with the primary influence of box 4 (HNF-1) and box 2 (HNF-4). A similar analysis in the HNF-free CHO cell line co-transfected with one or several HNF factors further demonstrated various interplays between boxes: box 3 (HNF-3 alpha and beta) has a negative influence over the major HNF-4 box 2 as well as a positive influence over the major HNF-1 box 4.